EVALUATING THE ROLE OF SDG 9 IN ECONOMIC GROWTH AND ENVIRONMENTAL SUSTAINABILITY: A QUANTITATIVE ANALYSIS - Maria Gheorghita, Rina Turcan, Alina Stratila (USV Annals of Economics and Public Administration)
The urgency of sustainable development resonates globally, promoting a balanced interaction between human advancement and environmental stewardship through the United Nations Sustainable Development Goals (SDGs). Of these goals, SDG 9 which emphasizes "Industry, Innovation, and Infrastructure" is vital for catalyzing economic growth and enhancing social and environmental sustainability. This research centers on SDG 9 within the European Union, aiming to elucidate its impact on sustainable development through rigorous analysis of industry, innovation, and infrastructure developments. This study employs comprehensive quantitative methodologies to assess the implications of SDG 9. Utilizing data from reputable international organizations, we conducted detailed statistical analyses using IBM SPSS Statistics to explore correlations and regressions among key performance indicators of SDG 9. The findings reveal a positive correlation between innovative activities, particularly in R&D, and economic outputs in sectors aligned with environmental goods and services. Regression analyses demonstrated a significant positive trend in the global SDG Index Score, particularly within SDG 9, indicating substantial progress from 2000 to 2022. This growth highlights the effectiveness of targeted measures in industry and infrastructure that have outpaced broader SDG achievements, suggesting that focused innovations and infrastructural investments can accelerate sustainable development. The EU's experience suggests that leveraging technology and innovation within these areas substantively contributes to broader sustainable development objectives, offering valuable insights for global policy strategies. This study underscores the necessity of integrating SDG 9 within a multifaceted approach to achieving comprehensive sustainability, enhancing policy implications that may guide future international efforts in sustainable development.